Elitical Participation in Planning Village Development - Vina Dini Pravita; Supardal Supardal (Jurnal Syntax Admiration, 2024)
The aim of this research is to determine the influence of electronic word of mouth (E-WOM) on repurchase intention mediated by brand image on Maybelline pressed powder products in Bandung City. The instruments used in this research have been declared to have passed the validity test, reliability test, classical assumption test, simple regression test, multiple regression test and Sobel test. This instrument is used as a data collection tool from respondents, namely consumers who use make up who have used and purchased products from the object being assessed. This research involved 165 respondents with ages ranging from 17 years and over. The data collection technique was carried out by distributing online questionnaires and the total time used to collect relevant data was cross-sectional or one shot study. The analytical tool used to test the data instrument uses SPSS version 25 software tools and the sobel test. The findings of this research show that electronic word of mouth (E-WOM) has a positive and significant effect on brand image, electronic word of mouth (E-WOM) has a positive and significant effect on repurchase interest, brand image has a positive and significant effect on repurchase interest , and brand image can mediate the influence of electronic word of mouth (E-WOM) on purchasing interest. The results of this research are also useful for managers of objects that are considered related, regarding designing strategies that are relevant to improving the quality of these attributes.